Practical guidelines for early screening and field evaluation of banana against Fusarium wilt, Pseudocercospora leaf spots and drought - Dita Rodriguez, Miguel Angel; Teixeira, Luiz; Li, Chunyu; Zheng, Sijun; O’Neill, Wayne; Daniels, Jeff; Pérez Vicente, Luis; Carreel, Françoise; Roussel, Véronique; Carlier, Jean; Abadie, Catherine; Carpentier, Sebastien C.; et al. (Bioversity International, 2021)
Practical guidelines for the early screening and field evaluation of banana (Musa spp.) for resistance to three major traits: Fusarium wilt (Fusarium oxysporum f. sp. cubense), leaf spot diseases (Pseudocercospora spp.) and drought. The guidelines have been produced by experts from the Evaluation Thematic Group of MusaNet, the global network for Musa genetic resources (www.musanet.org) coordinated by the Alliance of Bioversity and CIAT.